Jesuit political thought : the Society of Jesus and the state, c. 1540-1640 - Höpfl, Harro (Ideas in context, 2004)
Harro Höpfl presents here a full-length study of the single most influential organized group of scholars and pamphleteers in early modern Europe (1540-1630), namely the Jesuits. He explores the academic and political controversies in which they were engaged in and their contribution to academic discourse around ideas of 'the state' and 'politics'. He pays particular attention to their actual teaching concerning doctrines for whose menacing practical implications Jesuits generally were vilified: notably tyrannicide, the papal power to depose rulers, the legitimacy of 'Machiavellian' policies in dealing with heretics and the justifiability of breaking faith with heretics. Höpfl further explores the paradox of the Jesuits' political activities being at once the subject of conspiratorial fantasies but at the same time being widely acknowledged as among the foremost intellects of their time, with their thought freely cited and appropriated. This is an important work of scholarship.